(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2023)
The economic dynamics that occur as a result of changes in the behavior patterns of Hindu community life in Bali due to modernization. Modernization has had an effect on the formation of jobs that have changed the lifestyle of society as a whole, which was previously complicated to become practical, materialistic and individualistic. Likewise in the manufacture of banten used in the celebration of religious holy days and Hindu religious rituals. The banten industry provides business opportunities for the community and causes transformation in the economy of the Hindu community in Bali due to the high demand for banten offerings. This phenomenon increases the ability of the Hindu community in Bali to be able to use their time and energy to generate income. Even so, innovation is needed from the Hindu community in Bali to be able to increase existing business opportunities through the next generation of young people, it is expected to be able to bring the community’s economy in a better direction and maintain the preservation of culture, customs and beliefs of Hindus in Bali.